(untitled) (KULT_online, 2021)
The volume Europe’s Crises and Cultural Resources of Resilience: Conceptual Explorations and Literary Negotiations edited by Polland et al. explores European crises and the resources required and/or utilized in encounters with them. Although the contributions to the volume vary in quality and depth, the book is a significant contribution to the emerging literature in the study of ‘resilience.’ With an interdisciplinary approach, the book illustrates the relevance of literature and culture in critical historical and socio-political situations.